E.U. paediatric MOG consortium consensus: Part 5 – Treatment of paediatric myelin oligodendrocyte glycoprotein antibody-associated disorders. (November 2020) - Bruijstens, Arlette L.; Wendel, Eva-Maria; Lechner, Christian; Bartels, Frederik; Finke, Carsten; Breu, Markus; Flet-Berliac, Lorraine; de Chalus, Aliénor; Adamsbaum, Catherine; Capobianco, Marco; Laetitia, Giorgi; Hacohen, Yael; et al.
Abstract: In recent years, the understanding about the different clinical phenotypes, diagnostic and prognostic factors of myelin oligodendrocyte glycoprotein-antibody-associated disorders (MOGAD) has significantly increased. However, there is still lack of evidence-based treatment protocols for acute attacks and children with a relapsing course of the disease. Currently used acute and maintenance treatment regimens are derived from other demyelinating central nervous system diseases and are mostly centre-specific. Therefore, this part of the Paediatric European Collaborative Consensus attempts to provide recommendations for acute and maintenance therapy based on clinical experience and evidence available from mainly retrospective studies. In the acute attack, intravenous methylprednisolone (IVMP) leads to a favourable outcome in the majority of patients and can be followed by tapering of oral steroids up to a maximum of three months to maintain the benefit of acute treatment by suppressing disease activity. Intravenous immunoglobulins (IVIG) and plasmapheresis constitute second-line therapies in case of insufficient response to IVMP. After a first relapse, maintenance treatment should be started in order to prevent further relapses and the possibility of permanent sequelae. Four first-line therapies consisting of rituximab (RTX), azathioprine, mycophenolate mofetil or monthly IVIG have been identified by the consensus group. In case of further relapses despite maintenance treatment, the consensus group recommends treatment escalation with RTX or IVIG, followed by combining those two, and ultimately adding maintenance oral steroids. Many open questions remain which need to be addressed in further international prospective evaluation of MOGAD treatment. This international collaboration is essential to expand the state of current knowledge. Highlights: Paediatric MOGAD patients typically respond rapidly to IVMP in the acute attack. IVIG and PLEX are second-line treatment options during acute attack. Maintenance therapy in paediatric MOGAD should be considered after first relapse. This E.U. expert consensus recommends IVIG, AZA, MMF or RTX as first-line options. Escalation of therapy is recommended in case of insufficient treatment response.